Pengaruh persepsi orang tua tentang pentingnya imunisasi terhadap imunisasi balita di masa pandemi Covid-19 - Nurul Kodriati; Putri Eka Mulyana Wahab; Bunga Bilbina Rizkika (Jurnal Cakrawala Promkes, 2023)
The Covid-19 pandemic has had a significant impact on health services, including basic immunisation for under five children. The goal of this study is to identify whether parents’ perception about the importance of immunisation for their children associate with immunisation of children during the Covid-19 pandemic. From June 2022 to June 2023, an online survey was conducted to parents of children under the age of five. Purposive sample with a 5% margin of error and a 95% confidence level resulting at least 370 minimal samples were required in this study. The logistic regression method was used to examine several factors associated with children’s immunisation during the Covid-19 pandemic including demographic factors, perception about the importance of immunisation, and access related factors. During the 2020 to 2022, 10.9% of respondents did not implement immunisation, and 0.8% stated that immunisation is not necessary for their children. During the Covid-19 pandemic, parents who believe immunisation is necessary were 10 times more likely to immunise their children under the age of five (95% CI: 5.9 - 20.5). The findings of this study suggest that community education and understanding should be maintained in order to ensure the parents understand the importance of immunisation and further to increase immunisation coverage.